2004
DOI: 10.1128/jvi.78.3.1525-1539.2004
|View full text |Cite
|
Sign up to set email alerts
|

Removal of N-Linked Glycosylation Sites in the V1 Region of Simian Immunodeficiency Virus gp120 Results in Redirection of B-Cell Responses to V3

Abstract: One mechanism of immune evasion utilized by human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) envelope glycoproteins is the presence of a dense carbohydrate shield. Accumulating evidence from in vitro and in vivo experiments suggests that alterations in N-linked glycosylation of SIV gp120 can enhance host humoral immune responses that may be involved in immune control. The present study was designed to determine the ability of glycosylation mutant viruses to redirect antibody responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 51 publications
1
61
0
2
Order By: Relevance
“…These structures suggest that changes in the N173/N160 glycosylation site may affect V1/V2 and V3 interactions, which in turn may influence trimer structure and Env-CCR5 interactions, since V3 forms part of the CCR5 binding site. N-linked glycans in the V1/V2 region have also been identified as determinants of neutralization sensitivity, fusion activity, and CD4-independent infection (18,(57)(58)(59)(60)(61)(62)(63)(64) and may alter the position of the V1/V2 loop (64). N481 is located in the outer domain of gp120, which is on the surface of the Env trimer, in close proximity to the CD4 binding loop.…”
Section: Resultsmentioning
confidence: 99%
“…These structures suggest that changes in the N173/N160 glycosylation site may affect V1/V2 and V3 interactions, which in turn may influence trimer structure and Env-CCR5 interactions, since V3 forms part of the CCR5 binding site. N-linked glycans in the V1/V2 region have also been identified as determinants of neutralization sensitivity, fusion activity, and CD4-independent infection (18,(57)(58)(59)(60)(61)(62)(63)(64) and may alter the position of the V1/V2 loop (64). N481 is located in the outer domain of gp120, which is on the surface of the Env trimer, in close proximity to the CD4 binding loop.…”
Section: Resultsmentioning
confidence: 99%
“…glycosylation sites either to occlude immunodominant but variable regions or to enhance the exposure of conserved neutralization epitopes, respectively (10,17,32,50,64,66); repositioning of conserved epitopes within more variable, but also more immunogenic, regions of the HIV Env (48, 51); design of non-HIV Env scaffold proteins that express epitopes of broadly neutralizing antibodies (11,18,19,39,62,63); molecular evolution-based approaches (24); generation of ancestral or consensus Env sequences (23,31,45,46,52); and others. Thus far, all of these approaches have had a very limited success in the elicitation of broad and potent neutralizing antibody responses against tier 2 HIV-1 viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have shown the profound effects of Nlinked glycans on the envelope gp120 of HIV or SIV on Ab and CD8 T cell responses to these Ags (31)(32)(33)(34)(35)(36)(37)(38), very little is known about how these glycans affect gp120 Ag processing and its MHC-II presentation to the CD4 T cells. Previous studies have shown that CD4 T cell epitopes tend to cluster at specific nonglycosylated gp120 regions that are flanked with multiple N-linked glycosylation sites (39,40), but it is not known how these N-glycans actually influence CD4 T cell recognition of gp120 epitopes.…”
Section: T He Importance Of Cd4 Helper T Lymphocytes In Controlling Vmentioning
confidence: 99%